Climate‐Driven Topographic Asymmetry Enhanced by Glaciers: Implications for Drainage Reorganization in Glacial Landscapes - Jingtao Lai; Kimberly Huppert (Geophysical Research Letters)
Abstract Climate contrasts across drainage divides, such as orographic precipitation, are ubiquitous in mountain ranges, and as a result, mountain topography is often asymmetric. During glacial periods, these climate gradients can generate asymmetric glaciation, which may modify topographic asymmetry and drive divide migration during glacial‐interglacial cycles. Here we quantify topographic asymmetry caused by asymmetric glaciation and its sensitivity to different climate scenarios. Using an analytical model of a steady‐state glacial profile, we find that the degree of topographic asymmetry is primarily controlled by differences in the equilibrium line altitude across the divide. Our results show that glacial erosion can respond to the same climate asymmetry differently than fluvial erosion. When there are precipitation differences across the divide, glacial erosion produces greater topographic asymmetry than fluvial erosion, all else equal. These findings suggest that glaciations may promote drainage reorganization and landscape transience in intermittently glaciated mountain ranges.